Improving android-based e-learning skills of Biology teachers in Enrekang Regency, South Sulawesi - Arifin, Arifah Novia; Bahri, Arsad; Suryani, A. Irma (Universitas Muhammadiyah Malang, 2020)
The era of the industrial revolution 4.0 changed the way of looking at education. The changes made are not just a way of teaching, but are far more essential that is in the perspective on the concept of education itself. The competence of Biology teachers in Enrekang Regency in designing learning tools and media based on Information and Communication Technology (ICT) is still low. This community partnership program activity aimed to improve the ability of high school biology teachers to use android-based e-book creation software. In the implementation of this training activity, the following results were obtained: (1) Increasing the ability of MGMP teachers for Biology subject in Enrekang Regency in designing Android-based e-book learning media, (2) As the assessment, an overall average score of this program was 4.93 (categorized as good criteria). Based on the results of this community partnership program, it is hoped that the results can be a good input for the Enrekang Regency Education office in particular, education practitioners and the government in general. To sum up, Â the ability of teachers related to the application of technology and information in learning activities using various technology utilization through sorts of trainings still need hard efforts to increase.